2018
DOI: 10.1159/000488273
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside 20(S)-Rg3 Inhibits the Warburg Effect Via Modulating DNMT3A/ MiR-532-3p/HK2 Pathway in Ovarian Cancer Cells

Abstract: Background/Aims: The Warburg effect is one of the main energy metabolism features supporting cancer cell growth. 20(S)-Rg3 exerts anti-tumor effect on ovarian cancer partly by inhibiting the Warburg effect. microRNAs are important regulators of the Warburg effect. However, the microRNA regulatory network mediating the anti-Warburg effect of 20(S)-Rg3 was largely unknown. Methods: microRNA deep sequencing was performed to identify the 20(S)-Rg3-influenced microRNAs in SKOV3 ovarian cancer cells. miR-532-3p was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…Our previous studies have found that 20(S)-Rg3 antagonized the Warburg effect in ovarian cancer and downregulates the two key glycolytic enzymes HK2 and PKM2 [5,6]. Mechanistic studies have revealed that 20(S)-Rg3 downregulates HK2 via STAT3 [5] or DNMT3A/miR-532-3p [6] pathways. But the mechanism of PKM2 downregulation induced by 20(S)-Rg3 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies have found that 20(S)-Rg3 antagonized the Warburg effect in ovarian cancer and downregulates the two key glycolytic enzymes HK2 and PKM2 [5,6]. Mechanistic studies have revealed that 20(S)-Rg3 downregulates HK2 via STAT3 [5] or DNMT3A/miR-532-3p [6] pathways. But the mechanism of PKM2 downregulation induced by 20(S)-Rg3 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…20(S)-Rg3 exhibits anti-tumor activity in various cancers via inducing apoptosis or weakening proliferation, migration and invasion of cancer cells [18][19][20]. Our previous studies have found that 20(S)-Rg3 antagonized the Warburg effect in ovarian cancer and downregulates the two key glycolytic enzymes HK2 and PKM2 [5,6]. Mechanistic studies have revealed that 20(S)-Rg3 downregulates HK2 via STAT3 [5] or DNMT3A/miR-532-3p [6] pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Rg3 inhibits tumor cell growth, invasion, metastasis, and neovascularization [22][23][24]. Glycolytic regulation by Rg3, a potential anticancer mechanism, has been previously reported [25,26]. Pharmacological studies also showed that Rg3 suppressed gastric cancer cell growth [27][28][29].…”
Section: Discussionmentioning
confidence: 99%